Workplace Bullying in U.S. Higher Education: Results from a Statewide Survey - Lemon, Kathy; Barnes, Kendra; Soumyaja, Devi (Advances in Social Sciences Research Journal, 2022)
The purpose of this study is to examine prevalence, characteristics and sociodemographic correlates of workplace bullying among tenure-track faculty at U.S. Higher Education Institutions. A sample of 930 faculty from 20 campuses in California completed an online survey that included the Negative Acts Questionnaire – revised. Findings indicated a high prevalence of self-labeled workplace bullying (43.6% now and then/rarely, and 8.4% daily/weekly). Bullying behaviors that ostracized and excluded the target were the most commonly reported types of abusive conduct. Work sabotage, high workloads, and spreading gossip were also reported at high rates. Female professors, people who were between the ages of 50-69, Native American/Other race/ethnicity, and those who were full professors with tenure had the highest prevalence rates. Being a target of workplace bullying tended to be a long-standing experience (44.4% had been experiencing the abuse for six or more years) and 49.7% of targets were bothered ‘a great deal’ by the bullying. Most respondents (82.8%) indicated that the Covid-19 shutdowns had no effect or decreased the bullying and 69.0% were not sure whether their campus had an anti-bullying policy. Implications for updated workplace policies that incorporate current research on abusive conduct are discussed, as well as the need for improvements in organizational cultures and leadership practices.